Assessment of BG-Pro (Biogent AG) and Silver Bullet 2.1 (Lumin8) UV-Light Traps Efficiency for Surveillance of Malaria Vectors in Western Kenya - Billy L. Amugune; Richard Tamre; Dylan Mogaka; Oscar Mbare; Tullu Bukhari; Ulrike Fillinger; Margaret M. Njoroge (Insects)
The Centers for Diseases Control (CDC) light trap is widely used for malaria vector surveillance, but its acquisition logistics pose challenges in Africa. Evaluating new traps can improve surveillance tools. This study compared the efficiency of the BG-Pro UV and Silver Bullet 2.1 UV (SB 2.1 UV) against the UV LED CDC trap in western Kenya’s rice irrigation area. The traps were tested indoors in eight houses over 64 nights. Light properties and fan speed were analyzed using spectrometry and an anemometer. The BG-Pro UV trap performed better than the UV LED CDC trap for An. gambiae s.l. (RR 2.0, 95% CI 0.9–3.9) and An. funestus s.l. (RR 3.5, 95% CI 1.9–6.4). The SB 2.1 UV trap was more effective in capturing An. gambiae s.l. (RR 4.3, 95% CI 2.5–7.3) and An. funestus s.l. (RR 7.1, 95% CI 3.9–13.1), and also caught three times more Culex spp. (RR 2.7, 95% CI 1.2–6.0). SB 2.1 UV had the highest downstream force, and all traps emitting UV-A light had consistent wavelengths. Overall, the BG-Pro and SB 2.1 traps’ trapping efficiency was three to six times more than the CDC trap, making them promising surveillance tools, particularly in low-density malaria settings.